Elites and masses: the prevalence of economics and culture in nineteenth-century American party platforms. Issue 1 (2nd January 2019) - Silver, Adam
ABSTRACT: Scholarship on political party development in nineteenth-century America has focused on the relationship between elites and voters on the influence of policy proposals. The question is how elite perception of voter demands influenced parties' ideological development. This study addresses this question by assessing the dynamic between cultural and socioeconomic concerns in party ideological formation and policy articulation. A content analysis of national and state party platforms from 1840 through 1896 sheds light on this dynamic. Ultimately, party leaders set the political agenda by referencing economic concerns to a greater degree than cultural concerns in their platforms.